A Correlation of Molecular Docking and ADME Studies on 5,5-diphenylimidazolidine-2,4-dione: Inhibitors of Human Voltage-Gated Sodium Channel (Nav1.2)-2KAV - Nikam, Pooja Anil; Shaikh, Shabnam Babu; Kokate, Girish Ravindra; Katore, Vanita Baban; Wani, Saiprasad Vasant; Shaikh, Sabafarin Hasin; Bhor, Rohit Jaysing (International Journal of Pharmaceutical Investigation, 2026)
Background The purpose of this work is to use Lipinski's rule to perform molecular docking and drug-likeness analysis of the proposed 5,5-diphenylimidazolidine-2,4-dione. One description claims that the most common chronic brain disorder is epilepsy. One typical indication of epilepsy is uncontrollable convulsions caused by temporary neuronal discharges. Many new anticonvulsants have been introduced to the Indian market, however despite the use of both new and old medications, many types of seizures have not yet been well managed with fewer adverse effects. Materials and Methods Molecular Design Suite was used to conduct Combi Lab investigations and 3D-QSAR. Schrodinger Maestro was used for the molecular docking investigation. Results In a combinatorial approach, three compounds (CA1-CA10) out of ten compounds showed better predicted biological activity than the most active molecule in the dataset. The amino acid residues on the human voltage-gated sodium channel (Nav1.2)-2KAV showed proximal interaction with these substances. Conclusion The drug-like properties of the suggested compounds were expected. All of the suggested compounds had good molecular docking and in silico ADME properties, and tests were conducted to determine their capacity to inhibit the Human Voltage-gated Sodium Channel (Nav1.2)-2KAV. According to molecular docking studies, all medications seemed to bind more positively with the target protein; these pharmaceuticals could be potent sodium channel inhibitors that function via a GABAergic route. 5,5-diphenylimidazolidine-2,4-dione analogs may be equally hazardous and potent anticonvulsants. GABAergic pathway production depends on the human voltage-gated sodium channel (Nav1.2)-2KAV, one of the key enzymes.
Keywords: Convulsion; ADMET; Molecular docking; Human Voltage-Gated Sodium Channel (Nav1.2)-2KAV